Runtime change management based on object oriented petri net - Rajabi, B.A.; Lee, S.P. (2009)
Change management is very important to reduce risks and costs and maximizes the benefits of such major changes in business and information technology. Business Process Modeling (BPM) technology continues to face challenges in coping with dynamic business environments where requirements and goals are constantly changing at the execution time. In this research, we propose a framework for change management technique based on the integration between Object Oriented (OO) diagramming technique and Petri Net (PN) modeling language to increase the representation capability for OO modeling for the dynamic changes in the runtime instances.